Reflections on anthropology : (McGraw-Hill, 2004)
An outstanding complement to any introductory textbook in general anthropology, this new reader provides a balanced presentation of all four fields. Its 44 articles focus on topics not usually covered in depth in general textbooks; more than half of the selections were published between 2000-2002, and many address controversial topics (e.g., ethnic labels, poverty, evolution, gender issues). The articles show how anthropology can help each person understand his/her heritage, and how each human culture is unique in some aspects and yet similar to others.